2010
DOI: 10.1177/1759720x09359728
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TNF therapy in ankylosing spondylitis: insights for the clinician

Abstract: The introduction of tumour necrosis factor (TNF)-blocking therapy has revolutionized the management of ankylosing spondylitis (AS) over the last decade. This review highlights the current evidence relating to the use of TNF-blocking therapy in AS. International guidelines for the use of TNF blockers in AS are summarized. An outline of the evidence for efficacy and safety of these drugs is included, highlighting recent data from registries and real-life observational studies. Such cohort data is also reviewed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…On the other hand, it has been shown that younger patients with short duration of disease and high functional status would benefit more from TNFi treatment because these patients present more acute inflammation but less irreversible structural damage has occurred . However, it has also been reported that TNFi are effective in controlling disease activity in advanced AS …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown that younger patients with short duration of disease and high functional status would benefit more from TNFi treatment because these patients present more acute inflammation but less irreversible structural damage has occurred . However, it has also been reported that TNFi are effective in controlling disease activity in advanced AS …”
Section: Discussionmentioning
confidence: 99%
“…Whereas TNF-TNF-R engagement is known to induce apoptosis, under certain conditions caspase-8-mediated processing of IL-1β and IL-18 is more prominent (20). Moreover, anti-TNF therapy has also been implicated as a potential therapeutic against inflammatory bone diseases in clinics (23,24 …”
Section: Tnf-signaling Pathway Does Not Engage Inflammatory Caspase 8mentioning
confidence: 99%
“…This suggests that cytokines produced by monocytes contribute to inflammation. An association between the serum levels of inflammatory mediators and disease activity in AS has been reported (32, 33) Moreover, therapeutic success of anti-TNF agents in both AS and ERA further supports the role of pro-inflammatory cytokines in SpA (34,35).…”
Section: Discussionmentioning
confidence: 85%